2022
DOI: 10.1302/0301-620x.104b8.bjj-2022-0119.r1
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial intelligence and computer vision in orthopaedic trauma

Abstract: Artificial intelligence (AI) is, in essence, the concept of ‘computer thinking’, encompassing methods that train computers to perform and learn from executing certain tasks, called machine learning, and methods to build intricate computer models that both learn and adapt, called complex neural networks. Computer vision is a function of AI by which machine learning and complex neural networks can be applied to enable computers to capture, analyze, and interpret information from clinical images and visual inputs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…18 Recent advances in artificial intelligence-based algorithms, predictive analytics, virtual reality, smart devices, and robotic arm-assisted surgery are proving to be invaluable adjuncts across various orthopaedic subspecialties. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Previously, the MDD could give fast-track approvals for these "Software as Medical Device" (SaMD) applications using substantial equivalence to existing products. However, it has been suggested that this fast-track application system created a loophole in the certification process for some technological innovations, with premature implementation of SaMD applications that compromised patient safety.…”
Section: The Impact Of the European Union's Medical Device Regulation...mentioning
confidence: 99%
“…18 Recent advances in artificial intelligence-based algorithms, predictive analytics, virtual reality, smart devices, and robotic arm-assisted surgery are proving to be invaluable adjuncts across various orthopaedic subspecialties. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Previously, the MDD could give fast-track approvals for these "Software as Medical Device" (SaMD) applications using substantial equivalence to existing products. However, it has been suggested that this fast-track application system created a loophole in the certification process for some technological innovations, with premature implementation of SaMD applications that compromised patient safety.…”
Section: The Impact Of the European Union's Medical Device Regulation...mentioning
confidence: 99%
“…3,37 AI is as good as its data, and the development of robust reporting frameworks is vital to preventing avoidable errors. 70,[76][77][78] Guidelines for establishing models are necessary, such as the Transparent Reporting of a multivariate prediction model for Individual Prognosis or Diagnosis (TRIPOD) initiative, 77 which has already been used in validating ML in orthopaedics. The complexity of CNNs usually depends upon the complexity of the input data.…”
Section: Rehabilitation and Postoperative Carementioning
confidence: 99%
“…[2][3][4][5][6] Their message should be heeded by all readers, regardless of their subspecialty. [7][8][9][10] If we are to see benefits for our patients, the questions addressed must be meaningful, the methodology must be rigorous, and the results must be reported transparently, appropriate data must be available, and each model of AI must be externally validated. The paper by Polisetty et al 1 and their recommendations, allied to our previous guidance, will be critical to the future evaluation and use of AI in arthroplasty surgery.…”
Section: Looking Back Over the Past Yearmentioning
confidence: 99%